The halo of regressing nevus is not always regular in children. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Halo nevus is expression of the regression/depigmentation of the nevus due to autoimmune inflammation. It involves both the nevus and in a very regular manner the surrounding skin. Here are reported four exceptional cases of depigmentation/regression of nevi. In these nevi the classic halo around the nevus lacks, the depigmentation around or inside the nevus is partial or regular inside the nevus around a more pigmented central portion of the nevus or finally completely irregular around a melanic lesion devoid of cells.